Dengue Virus Type 2 NS3 Protease and NS2B-NS3 Protease Precursor induce Apoptosis - Shafee, N.; AbuBakar, Sazaly (2003)
Apoptosis was detected in Vero cell cultures expressing transfected dengue virus type 2 (DENV-2) genes. Approximately 17(.)5 and 51(.)5 of cells expressing NS3 serine protease and NS2B-NS3(185) serine protease precursor protein NS2B-NS3(185)(pro) genes, respectively, were apoptotic. The percentage of apoptotic cells was significantly higher in cell cultures expressing NS2B-NS3(185)(pro). NS2B-NS3(185)(pro) was detected as NS2B-NS3(185)(pro)-EGFP fusion protein in cytoplasmic vesicular structures in the apoptotic cells. Site-directed mutagenesis which replaced His 51 with Ala within the protease catalytic triad significantly reduced the ability of the expressed NS3 and NS2B-NS3(185)(pro) to induce apoptosis. Results from the present study showed that DENV-2-encoded NS3 serine protease induces apoptosis, which is enhanced in cells expressing its precursor, NS2B-NS3(185)(pro). These findings suggest the importance of NS2B as a cofactor to NS3 protease-induced apoptosis.